2015
DOI: 10.3389/fneur.2015.00268
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vestibular Disorder in Older People Who Experience Dizziness

Abstract: Dizziness and imbalance are clinically poorly defined terms, which affect ~30% of people over 65 years of age. In these people, it is often difficult to define the primary cause of dizziness, as it can stem from cardiovascular, vestibular, psychological, and neuromuscular causes. However, identification of the primary cause is vital in determining the most effective treatment strategy for a patient. Our aim is to accurately identify the prevalence of benign paroxysmal positional vertigo (BPPV), peripheral, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…A previous population-based clinical study in the United Kingdom reported that 30% of people older than 65 years have dizziness or vertigo [16]. Many previous studies demonstrated that peripheral vestibular dysfunction is the most frequent cause of dizziness in the elderly, and BPPV constitutes one of the most common peripheral vestibular disorders [5,7,17,18]. BPPV can arise in various etiological factors, but idiopathic occurrence is the most frequent cause and the incidence is increasing with aging [8,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous population-based clinical study in the United Kingdom reported that 30% of people older than 65 years have dizziness or vertigo [16]. Many previous studies demonstrated that peripheral vestibular dysfunction is the most frequent cause of dizziness in the elderly, and BPPV constitutes one of the most common peripheral vestibular disorders [5,7,17,18]. BPPV can arise in various etiological factors, but idiopathic occurrence is the most frequent cause and the incidence is increasing with aging [8,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that older patients with BPPV have a more protracted course and higher risk of recurrence, but the causes of recurrence are not well understood [2,[4][5][6][7][8]. There are reports that aging contributes to the fragmentation of otoconia, as idiopathic BPPV (iBPPV) is more common in older adults than in younger individuals [8,12].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Balance ability involves the visual, vestibular, and somatosensory systems [7]. Recently, studies on the relation between balance and the vestibular system have described age-related changes [12][13][14], and several studies suggested that age-associated reductions in vestibular function are caused by loss of neurons and vestibular hair cells in vestibular nuclei and diminished vestibuloocular reflex gain [13,15]. The structures that mediate these vestibular functions are considered important, and structures of the central vestibular form are considered to be especially important [16].…”
Section: Introductionmentioning
confidence: 99%